Hassan Hanafi: Biografi dan Pemikiran Teologinya - Halimah SM (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2007)
Hassan Hanafi was a renowned Egyptian thinker and reformer known for the concept of Islamic Left. Islamic Left emerged when various methods of renewing Muslim societies over several generations yielded only relative success, and for some, outright failure, especially in addressing issues of underdevelopment. Islamic Left drew inspiration from the surprising success of the Islamic revolution in Iran, which captivated the world. Islamic Left sought to develop religious reform not only in confronting contemporary threats such as colonialism, protectionism, capitalism, underdevelopment, and oppression, as championed by al-Afghani. It also aimed at the reconstruction of the reformatory religious thought itself.